A Theoretical Perspective on Strategies for Modeling High Performance Nonlinear Optical Materials - Bano, Rehana; Asghar, Maria; Ayub, Khurshid; Mahmood, Tariq; Iqbal, Javed; Tabassum, Sobia; Zakaria, Rozalina; Gilani, Mazhar Amjad (Frontiers in Materials, 2021)
Nonlinear optical (NLO) materials have spanned a large area of science and technology owning to their potential applications in optoelectronics. Invention of first Ruby has sparked fresh interest to the area of nonlinear optics. Computational designing and experimental synthesis of organic and inorganic NLO materials with higher order nonlinearities come into vogue in materials science. To date, several strategies including push pull mechanism, metal ligand framework, diradical character and so on have been devised for the enhancement of NLO response of materials. In addition, introduction of diffuse excess electrons is an efficient approach to design noncentrosymmetric materials for nonlinear optics. The current review establishes a systematic array of different studies (covering over last decade of intensive research work) for the theoretical designing of NLO materials. In the present review, theoretical designing from the simplest NLO material to the complex alkali, alkaline earth, transition and superalkali doped nanomaterials is summarized. Excess electrons of the nanoclusters have played a pivotal role in enhancing the NLO properties especially hyperpolarizabilities. We expect that this review will provide a better understanding of the NLO responses of nanoclusters, paving the way for the development of high performance NLO materials to meet real challenges in the optoelectronics.